To Study the Consumer Attitude Towards Purchase Intention of Online Courses on Udemy Using Co-Relation with Reference to English Speaking and Excel Among Gen-Z in Ahmedabad - Chandni J. Vidani; Shashwat Sharma (International Journal of Managemen Analytics (IJMA), 2023)
This research aims to examine the consumer attitude toward the purchase intention of online courses on Udemy among Gen-Z individuals in Ahmedabad, specifically focusing on English speaking and Excel courses. The Gen-Z population, born between the mid-1990s and early 2000s, is known for its digital savviness and preference for online learning. As online education platforms like Udemy have gained significant popularity, it becomes crucial to understand the consumer attitudes that drive their purchase intentions. The questionnaire will measure consumer attitudes towards online courses on Udemy, including factors such as Perceived utility, perceived convenience of use, course quality, and instructor trustworthiness are all factors to consider Respondent's readiness to pay for English speaking and Excel classes will be used to determine purchase intent. Data collected from the survey will be analyzed using correlation analysis to examine the relationship between consumer attitudes and purchase intention. The findings will provide insights into the factors that influence Gen-Z's decision-making process when considering online course purchases on Udemy.  The study will help us understand the significance of English speaking and Excel courses in this demographic's educational preferences. The results of this research will be beneficial for online education platforms, course creators, and marketers to enhance their offerings and marketing strategies, ultimately catering to the needs and preferences of Gen-Z learners in Ahmedabad